Obtenção de nanocelulose bacteriana de kombucha - Góes, Thaís Soares de (Universidade Federal de São Carlos, 2020)
In the last years, sustainable materials that provide less environmental impact are gaining special attention. In this context, cellulose, a natural and abundant polymer from several renewable vegetable and microbial sources, is being highlighted in related literature. Bacterial cellulose (BC) from microbial sources presents several advantageous properties as lignin and hemicellulose absence, high resistance to traction, elasticity, durability, and a high degree of crystallinity. Also, BC is biodegradable, non-toxic, and biocompatible. A less explored source of BC includes Kombucha membranes (KM), a by-product of Kombucha's ancient beverage. KM are cellulosic pellicles derived from the fermentation of black or green tea broth. Thus, the main objective of this study was the production and characterization of the physical and chemical properties of BC obtained from Kombucha’s bacterial cellulose membranes (KBCM) based on the fermentation of green tea broth with added sucrose. We also aimed at the production of bacterial nanocellulose from Kombucha beverage (BNKB) via a hydrolytic reaction. KBCM was produced using a symbiotic consortium of bacteria and yeast during the fermentation of green tea broth and sucrose inoculated with an initial KBCM solution and fermented at 35°C for 21 days. After, the KBCM solution was purified using distilled water and sodium hydroxide (NaOH). BKNB were extracted via KBCM acid hydrolysis with 64% sulfuric acid at 50°C, and reaction time variation, followed by dialysis processes until reach a neutral pH value. KBCM were analyzed before and after the purification process using atomic force microscopy (AFM), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), Fourier transform infrared (FTIR) spectroscopy, and X-ray diffraction (XRD). Suspensions containing BNKB were characterized by AFM only. KBCM before and after purification were characterized by the techniques of atomic force microscopy (AFM), scanning electron microscopy (SEM), dispersive energy spectroscopy (EDS), infrared absorption spectroscopy with Fourier transform (FTIR) and Diffraction X-ray (XRD). BNKB suspensions were characterized only by AFM. AFM and SEM analyzes revealed the morphology of the BNKB structures in long fibrous chains, which were clustered and interlaced. The relative intensities by XRD varied after the purification process, indicating a possible change in crystallinity. The presence of carbon and oxygen elements in KBCM before and after purification were also confirmed by EDS. Thus, it is concluded that through the mentioned characteristics and the BNKB morphology, they offer resistance in their cellulosic chains during the acid attack, which can be observed by the AFM images, due to the presence of curvatures in the KC nanofibrils, which by time it leverages it as a promising source of raw material for the production of new sustainable materials.
Obtaining of bacterial nanocellulose from kombucha
Keywords: Celulose bacteriana; Biopolímero; Fontes renováveis; Nanociência; Nanoscience; Renewable sources; Bacterial cellulose; Biopolymers; CIENCIAS EXATAS E DA TERRA::QUIMICA